GIS in Sustainable Urban Planning and Management: A Global Perspective (Taylor & Francis, 2019)
GIS is used today to better understand and solve urban problems. This book explores and illustrates the use of geo-information in the planning and management of urban regions. The first part of the book addresses the concept of sustainable urban development, its different frameworks, the many ways of measuring sustainability, and its value in the urban policy arena. The second part discusses how urban planning can shape our cities, examines various spatial configurations of cities, the spread of activities, and the demands placed on different functions to achieve strategic objective. It further focuses on the recognition that urban dwellers are increasingly under threat from natural hazards and climate change.